Diseases of the Sinuses A Comprehensive Textbook of Diagnosis and Treatment - Chang, Christopher C.; Incaudo, Gary A.; Gershwin, M. Eric (Springer New York : Imprint: Springer, 2014)
Diseases of the Sinuses: A Comprehensive Textbook of Diagnosis and Treatment, 2nd Edition, offers the definitive source of information about the basic science of the sinuses and the clinical approach to sinusitis.  Since the widely praised publication of the first edition, understanding of sinus disease has changed dramatically, mainly as a result of recent developments and new discoveries in the field of immunology.  This updated and expanded edition is divided into sections addressing, separately, the pathogenesis, clinical presentation, medical and surgical management of acute and chronic rhinosinusitis.  Special entities such as autoimmune-related sinusitis, allergy and sinusitis, and aspirin-exacerbated respiratory disease are discussed in separate chapters. The role of immunodeficiency is also addressed. The management section has been fully updated to incorporate new medical modalities and surgical procedures.  Developed by a distinguished group of international experts who share their expertise and insights from years of collective experience in treating sinus diseases, the book will appeal to anyone who has an interest in sinus disease, including both physicians and allied health professionals. Internists, pediatricians, allergists, otolaryngologists and infectious disease specialists will find the book to be an invaluable, comprehensive reference. Physician assistants and nurse practitioners who work with specialists who treat sinus disease will also benefit from the book.